Identifying nontechnical skills associated with safety in the emergency department: a scoping review of the literature. - Flowerdew, L; Brown, R; Vincent, C; Woloshynowych, M (2012)
STUDY OBJECTIVE: Understanding the nontechnical skills specifically applicable to the emergency department (ED) is essential to facilitate training and more broadly consider interventions to reduce error. The aim of this scoping review is to first identify and then explore in depth the nontechnical skills linked to safety in the ED. METHODS: The review was conducted in 2 stages. In stage 1, online databases were searched for published empirical studies linking nontechnical skills to safety and performance in the ED. Articles were analyzed to identify key ED nontechnical skills. In stage 2, these key skills were used to generate additional key words, which enabled a second search of the literature to be undertaken and expand on the evidence available for review. RESULTS: In stage 1, 11 articles were retrieved for data analysis and 9 core emergency medicine nontechnical skills were identified. These were communicating, managing workload, anticipating, situational awareness, supervising and providing feedback, leadership, maintaining standards, using assertiveness, and decisionmaking. In stage 2, a secondary search, using these 9 skills and related terms, uncovered a further 21 relevant articles. Therefore, 32 articles were used to describe the main nontechnical skills linked to safety in the ED. CONCLUSION: This article highlights the challenges of reviewing a topic for which the terms are not clearly defined in the literature. A novel methodological approach is described that provides a structured and transparent process for reviewing the literature in emerging areas of interest. A series of literature reviews focusing on individual nontechnical skills will provide a clearer understanding of how the skills identified contribute to safety in the ED.